Nature and commerce in northern Brazil: “Discurso sobre os gêneros para o comércio, que há no Maranhão e Pará” by Duarte Ribeiro de Macedo (1633) - Cardoso, Janaina Salvador [UNESP] (FapUNIFESP (SciELO), 2022)
Duarte Ribeiro de Macedo may be the best-known scholar that contemplated the Portuguese economy in the seventeenth century. Macedo had degrees in law and philosophy, and wrote various texts on the introduction of manufacturing and best way to utilize the natural resources found in Portugal’s colonies. In Discurso sobre os gêneros para o comércio, que há no Maranhão e Pará [Discussion on the genera in Maranhão and Pará for trade] (1633), he introduces 37 plants with superior economic potential that were available in Maranhão and Pará. Here this groundbreaking manuscript is transcribed, and Macedo’s suggestions about the economic potential of Maranhão are introduced.
Natureza e comércio no norte do Brasil: O “Discurso sobre os gêneros para o comércio, que há no Maranhão e Pará” de Duarte Ribeiro de Macedo (1633)
Keywords: Colonial trade; History of the Portuguese Americas; Natural resources; State of Maranhão and Grão-Pará